The meaning of Protestant theology : Luther, Augustine, and the Gospel that gives us Christ - Cary, Phillip, 1958- (Grand Rapids,MI Baker Academic, 2019)
This book offers a creative and illuminating discussion of Protestant theology, helping readers rethink their own theology and its place in the larger story of Christian thought. Veteran teacher Phillip Cary, an internationally acclaimed expert on Augustine and Augustine's thought, explains how Luther's theology arose from the Christian tradition, particularly from the spirituality of Augustine. Luther departed from the Augustinian tradition and inaugurated distinctively Protestant theology when he identified the gospel that gives us Christ as its key concept. More than any other theologian, Luther succeeds in carrying out the Protestant intention of putting faith in the gospel of Christ alone. Cary also explores the consequences of Luther's teachings as they unfold in the history of Protestantism. This work will appeal to professors and students of theology, pastors, and laypeople.
Introduction: Why Protestantism? -- Philosophical Spirituality -- Divine Carnality -- Christ the Mediator in Augustine -- The Augustinian Journey and Its Anxieties -- Young Luther: Justification as Penitential Process -- Young Luther: Justification without Gospel -- Luther the Reformer: Gospel as Sacramental Promise -- Luther the Reformer: Gospel as Story That Gives Us Christ -- Scripture: Demanding the Wrong Kind of Certainty -- Salvation: Faith in Christ's Promise Alone -- Sacrament: Turning Outward to Divine Flesh -- Trinity: God Giving Himself in Person -- Conclusion: Why Luther's Gospel? -- Appendix 1: Luther's devils -- Appendix 2: Gospel as Sacrament: Luther's Sermon on Christmas Day 1519.
Includes bibliographical references (pages 355-364) and index.
Keywords: Luther, Martin, -- 1483-1546.; Augustine, -- of Hippo, Saint, -- 354-430 -- Influence; Theology, Doctrinal -- History -- 16th century; Protestantism; Protestant churches -- Doctrines -- History